Machine-learning model predicting postoperative delirium in older patients using intraoperative frontal electroencephalographic signatures - Röhr, Vera; Blankertz, Benjamin; Radtke, Finn M.; Spies, Claudia; Koch, Susanne (Frontiers in Aging Neuroscience, 2022)
Objective: In older patients receiving general anesthesia, postoperative delirium (POD) is the most frequent form of cerebral dysfunction. Early identification of patients at higher risk to develop POD could provide the opportunity to adapt intraoperative and postoperative therapy. We therefore propose a machine learning approach to predict the risk of POD in elderly patients, using routine intraoperative electroencephalography (EEG) and clinical data, readily available in the operating room. Methods: We conducted a retrospective analysis of the data of a single-center study at the Charité-Universitätsmedizin Berlin, Department of Anesthesiology [ISRCTN 36437985], including 1277 patients older than 60 years with planned surgery and general anesthesia. In order to deal with class imbalance, we used balanced ensemble methods, specifically Bagging and Random Forests and as a performance measure, the area under the ROC curve (AUC-ROC). We trained our models including clinical parameters and intraoperative EEG features in particular spectral and burst suppression signatures as well as multi-band covariance matrices, which were classified using the geometry of a Riemannian manifold. The models were validated with 10 repeats of a 10-fold cross-validation. Results: Including EEG data in the classification resulted in a robust and reliable risk evaluation for POD. The clinical parameters alone achieved a AUC-ROC score of 0.75. Including EEG signatures improved the classification, when the patients were grouped by anesthetic agents and evaluated separately for each group. The spectral features showed an AUC-ROC score of 0.66; the covariance features an AUC-ROC score of 0.68. The AUC-ROC scores of EEG features relative to patient data differed by anesthetic group. The best performance was reached combining both the EEG features and the clinical parameters. Overall, the AUC-ROC score was 0.77, for patients receiving Propofol 0.78, for those receiving Sevoflurane 0.8 and for those receiving Desflurane 0.73. Applying the trained prediction model to an independent data set of a different clinical study confirmed these results for the combined classification, while the classifier on clinical parameters did not generalize. Conclusion: A machine learning approach combining intraoperative frontal EEG signatures with clinical parameters could be an easily applicable tool to early identify patients at risk to develop POD.